Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
Ta có: \(2ab+c=\dfrac{4ab+1-2a-2b}{2}=\dfrac{\left(2a-1\right)\left(2b-1\right)}{2}\)
Và: \(a+b=\dfrac{1-2c}{2}\)
\(\Rightarrow\left(a+b\right)^2=\dfrac{\left(2c-1\right)^2}{4}\)
Thế vô bài toán ta được
\(P=\dfrac{2ab+c}{\left(a+b\right)^2}.\dfrac{2bc+a}{\left(b+c\right)^2}.\dfrac{2ca+b}{\left(c+a\right)^2}\)
\(=\dfrac{\dfrac{\left(2a-1\right)\left(2b-1\right)}{2}}{\dfrac{\left(2c-1\right)^2}{4}}.\dfrac{\dfrac{\left(2b-1\right)\left(2c-1\right)}{2}}{\dfrac{\left(2a-1\right)^2}{4}}.\dfrac{\dfrac{\left(2c-1\right)\left(2a-1\right)}{2}}{\dfrac{\left(2b-1\right)^2}{4}}\)
\(=\dfrac{4.4.4}{2.2.2}=8\)
cho \(c^2+2ab-2ac-2bc\)
rút gọn biểu thức \(P=\frac{a^2+\left(a-c\right)^2}{b^2+\left(b-c\right)^2}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(a+b+c=0\Rightarrow\hept{\begin{cases}a+b=-c\\b+c=-a\\a+c=-b\end{cases}}\)
\(\Rightarrow A=c^2ab+a^2bc+b^2ac=abc\left(a+b+c\right)=0\)